IECON'01. 27th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.37243)
DOI: 10.1109/iecon.2001.975866
|View full text |Cite
|
Sign up to set email alerts
|

Study of bifurcation and chaos in the current-mode controlled buck-boost DC-DC converter

Abstract: This paper derives an iterative map for the Buck-Boost converter under current-mode control. On the basis of the model, the bifurcation phenomena under variation of a range of circuit parameters including input voltage, reference current and load resistance, have been investigated. The simulation results including the strange attractors, bifurcation diagrams and waveforms are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Two‐dimensional discrete time model of a buck–boost converter is derived in . A more realistic discrete time model is developed in this section, considering parasitic elements like inductor resistance and capacitor resistance.…”
Section: Nonlinear Dynamics Analysis Of Boost and Buck–boost Convertersmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional discrete time model of a buck–boost converter is derived in . A more realistic discrete time model is developed in this section, considering parasitic elements like inductor resistance and capacitor resistance.…”
Section: Nonlinear Dynamics Analysis Of Boost and Buck–boost Convertersmentioning
confidence: 99%
“…To the best of our knowledge, very few researchers have concentrated on the potential of power electronics‐based chaotic DC‐DC converters in secure communication. Power electronics‐based DC‐DC converters, when used in feedback configuration, have been reported to exhibit nonlinear behavior . The only useful application reported of nonlinear dynamics like chaos in DC‐DC converters is electromagnetic interference mitigation .…”
Section: Introductionmentioning
confidence: 99%
“…In past years, due to nonlinear features of electronic components such as MOSFE T and diodes, there are most power electronic circuits that exhibit a wide range of bifurcation and chaotic behavior under switching nonlinearity. Nonlinear phenomena in buck, boost and buck-boost DC-DC converters have been widely studied for twenty years [1][2][3][4][5][6][7][8].…”
Section: State Equations Of Flyback Convertermentioning
confidence: 99%
“…00 ©20 1 0 IEEE input to a DC output at a lower voltage [6]. In litera ture, it has been reported that the switching operations of DCIDC converters in all their types (buck [1, 3,1 1], boost [2,5], buck-boost [9], C uk [4]) and structures (parallel connected [2,13], multi-cell [1,3]) exhibit a wide range of bifurcations and chaos, when some parameters are varied. To stabilize the chaotic behavior, several control methods are presented.…”
Section: Introductionmentioning
confidence: 99%